Herding Behavior Post Initial Public Offering In Indonesia Stock Exchange - Ike Arisanti; Marwan Asri (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
This research was conducted to test whether there is a herding behavior post Initial Public Offering (IPO) in Indonesia Stock Exchange. Domestic transactions on the Indonesia Stock Exchange are rising year by year along with the increased of IPO emissions. The existence of underpricing phenomenon causes a domino effect (herding) that arises on potential investors after the IPO. This study used Cross-Sectional Absolute Deviation (CSAD) method to detect herding behavior. The data used were daily price data of IPO shares from the 1st day until the 30th day after IPO period 2005-2015. Hypothesis testing was done using regression analysis by means of CSAD variable as dependent variable and return market as independent variable. The result of this research indicated that there was a herding behavior post -IPO in Indonesia Stock Exchange period 2005-2015 period. It is shown by the negative and significant value of γ2 (0.013 0.05).